UJI BEBERAPA KONSENTRASI EKSTRAK TEPUNG DAUN SRIKAYA (Annona squamosa L.) UNTUK MENGENDALIKAN HAMA Aphis gossypii Glover PADA TANAMAN CABAI - Hafiz Fauzana; Rizky Aulina Harahap (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Aphis gossypii Glover is the main pest that attacks chili plants. Control efforts that are often carried out are by using synthetic insecticides. Safe pest control is the use of vegetable insecticides. Srikaya is a plant that can be used as a botanical insecticide. The purpose of this study was to obtain an effective concentration of srikaya leaf powder extract against A. gossypii pest mortality. This research was conducted at the Plant Pest Laboratory of the Faculty of Agriculture, Riau University from March to July 2019. The study was conducted experimentally using a completely randomized design (CRD) with 6 treatments and 4 replications. The treatments given were extracts of srikaya leaf flour with the following concentrations: Srikaya flour with a concentration of 0 g.l-1 water, 20 g.l-1 water, 40 g.l-1 water, 60 g.l-1 water, 80 g.l-1 water, 100 g.l-1 water. The parameters observed were the initial time of death of Aphis gossypii, Lethal time 50 (LT50), daily mortality, total mortality, Lethal concentration (LC50), temperature and humidity. The results of this study indicate that the application of the extract of srikaya leaf flour (Annona squamosa L.) on concentration of 40 gl-1 srikaya leaf meal was an effective concentration to control A. gossypii which can cause total mortality of 82.5% with LC 50% is 1.37% or equivalent to 13.7 gl-1, and the right concentration to kill. 95% of pests is 6.37% or equivalent to 63.7 gl-1.